The operating room nurse, AIDS, and the law - Rozovsky, Lorne (Operating Room Nurses Association of Canada Journal, 1987)
The threat of the incurable killer AIDS has many health professionals worried about their legal responsibilities. Operating room nurses being more likely to face exposure than many others, must be especially aware.